2020
DOI: 10.1002/hed.26591
|View full text |Cite
|
Sign up to set email alerts
|

Chronic opioid use after laryngeal cancer treatment

Abstract: Background: Survivors of head and neck cancer may be at increased risk for chronic opioid use and questions remain about risk factors. Methods: Retrospective study of patients with laryngeal cancer prescribed opioids utilizing the Truven Health Marketscan database. Patients had laryngeal cancer, underwent treatment, filled an opioid prescription, and were enrolled in this private insurance plan 1 year prior to and after treatment. Results: In this study, 7484 patients were included; 17.2% developed chronic opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Several factors that we found to be associated with being prescribed moderate and high dose opioid therapy at 24-months post treatment were consistent with other literature. We found that those with pre-cancer substance use disorders or opioid prescriptions have an increased risk with lasting moderate dose opioid use, which is consistent with recent literature 38,39 in which being prescribed opioids before cancer, having a history of opioid use disorder, 7,21 a history of tobacco use, 7,21,24,40 or a history of alcohol use 7 were each associated with chronic opioid use 12-months post-diagnosis. 7,21,24,40 Taken together, patients with premorbid mental health and SUD characteristics may benefit from focused pain screening and alternative pain management efforts before, during and directly following cancer treatment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Several factors that we found to be associated with being prescribed moderate and high dose opioid therapy at 24-months post treatment were consistent with other literature. We found that those with pre-cancer substance use disorders or opioid prescriptions have an increased risk with lasting moderate dose opioid use, which is consistent with recent literature 38,39 in which being prescribed opioids before cancer, having a history of opioid use disorder, 7,21 a history of tobacco use, 7,21,24,40 or a history of alcohol use 7 were each associated with chronic opioid use 12-months post-diagnosis. 7,21,24,40 Taken together, patients with premorbid mental health and SUD characteristics may benefit from focused pain screening and alternative pain management efforts before, during and directly following cancer treatment.…”
Section: Discussionsupporting
confidence: 90%
“…We found that those with pre-cancer substance use disorders or opioid prescriptions have an increased risk with lasting moderate dose opioid use, which is consistent with recent literature 38,39 in which being prescribed opioids before cancer, having a history of opioid use disorder, 7,21 a history of tobacco use, 7,21,24,40 or a history of alcohol use 7 were each associated with chronic opioid use 12-months post-diagnosis. 7,21,24,40 Taken together, patients with premorbid mental health and SUD characteristics may benefit from focused pain screening and alternative pain management efforts before, during and directly following cancer treatment. In non-cancer pain management, there is a growing body of literature suggesting that brief pain management interventions prior to surgery decreases postoperative pain and may decrease need for opioid prescriptions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Surgery for head and neck cancer can also significantly impair a patient’s ability to perform daily activities, such as speaking and eating, with potential psychosocial consequences; in fact, up to 50%6 of these patients also suffer from depression and anxiety 4 5. Together, these factors inherently increase the risk of opioid dependence in this patient population, which may be as high as 20%–60% of patients after surgery for head and neck cancer 31 36–38. Additionally, both depression and chronic opioid use in cancer patients have been associated with poorer disease-free and overall survival 31–33…”
Section: Ethics and Disseminationmentioning
confidence: 99%